Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 9 - Sections 9.1-9.6 - Integrated Review - Functions and Properties of Logarithms: 6


$3\sqrt x-1$

Work Step by Step

We know that $(g°f)(x)=g(f(x))$. We know that $f(x)=\sqrt x$ and $g(x)=3x-1$. Therefore, $g(f(x))=g(\sqrt x)=3\sqrt x-1$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.